The Feasibility of Deriving the Electronic Frailty Index from Australian General Practice Records - Lewis ET; Williamson M; Lewis LP; Ní Chróinín D; Dent E; Ticehurst M; Peters R; Macniven R; Cardona M (Clinical Interventions in Aging, 2022)
Ebony T Lewis,1– 3 Margaret Williamson,1,4 Lou P Lewis,5 Danielle Ní Chróinín,6,7 Elsa Dent,8 Maree Ticehurst,5,9 Ruth Peters,2,3 Rona Macniven,1 Magnolia Cardona10,11 1School of Population Health, Faculty of Medicine & Health, University of New South Wales, Sydney, NSW, Australia; 2School of Psychology, Faculty of Science, University of New South Wales, Sydney, NSW, Australia; 3Neuroscience Research Australia (NeuRA), Sydney, NSW, Australia; 4Centre for Primary Health Care and Equity, Faculty of Medicine & Health, University of New South Wales, Sydney, NSW, Australia; 5Matraville Medical Centre, Sydney, NSW, Australia; 6Department of Geriatric Medicine, Liverpool Hospital, Sydney, NSW, Australia; 7South Western Sydney Clinical School, University of New South Wales, Sydney, NSW, Australia; 8Torrens University Australia, Adelaide, SA, Australia; 9Royal Prince Alfred Hospital, Sydney, NSW, Australia; 10Institute for Evidence-Based Healthcare, Faculty of Health Sciences and Medicine, Bond University, Gold Coast, QLD, Australia; 11Gold Coast Hospital and Health Service, Gold Coast, QLD, AustraliaCorrespondence: Ebony T Lewis, School of Population Health, Faculty of Medicine & Health, University of New South Wales, Level 3, Samuels Building, Gate 11, Botany Street, Sydney, NSW, 2052, Australia, Tel +612 9065 2068, Email ebony.lewis@unsw.edu.auPurpose: Frailty is a prevalent condition in older adults. Identification of frailty using an electronic Frailty Index (eFI) has been successfully implemented across general practices in the United Kingdom. However, in Australia, the eFI remains understudied. Therefore, we aimed to (i) examine the feasibility of deriving an eFI from Australian general practice records and (ii) describe the prevalence of frailty as measured by the eFI and the prevalence with socioeconomic status and geographic remoteness.Participants and Methods: This retrospective analysis included patients (≥ 70 years) attending any one of > 700 general practices utilizing the Australian MedicineInsight data platform, 2017– 2018. A 36-item eFI was derived using standard methodology, with frailty classified as mild (scores 0.13– 0.24); moderate (0.25– 0.36) or severe (≥ 0.37). Socioeconomic status (Socio-Economic Indexes for Areas (SEIFA) index)) and geographic remoteness (Australian Statistical Geography Standard (ASGC) remoteness areas) were also examined.Results: In total, 79,251 patients (56% female) were included, mean age 80.0 years (SD 6.5); 37.4% (95% CI 37.0– 37.7) were mildly frail, 16.7% (95% CI 16.4– 16.9) moderately frail, 4.8% (95% CI 4.7– 5.0) severely frail. Median eFI score was 0.14 (IQR 0.08 to 0.22); maximum eFI score was 0.69. Across all age groups, moderate and severe frailty was significantly more prevalent in females (P < 0.001). Frailty severity increased with increasing age (P < 0.001) and was strongly associated with socioeconomic disadvantage (P < 0.001) but not with geographic remoteness.Conclusion: Frailty was identifiable from routinely collected general practice data. Frailty was more prevalent in socioeconomically disadvantaged groups, women and older patients and existed in all levels of remoteness. Routine implementation of an eFI could inform interventions to prevent or reduce frailty in all older adults, regardless of location.Keywords: primary health care, family practice, frailty, electronic health records, geriatric assessment, aged